Ekosistem Radio Siaran Swasta di Pekanbaru pada Era Penyiaran Digital - Harry Setiawan; Benni Handayani; Angelina Fransisca Sherlya (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2023)
Broadcasting in Indonesia experienced significant progress by technology migration (analog switch-off/ ASO). Unfortunately, the announced migration does not apply to radio broadcasting technology. The broadcast radio ecosystem before ASO experienced a decline, coupled with the exclusion of radio from major broadcasting decisions. This research used an interpretive paradigm and a case study approach on private broadcasting radio ecosystem in Pekanbaru. It was carried out using convergent mixed research methods and the theory of media ecology and actor-network theory and involved 204 listeners as informants who were approached by road surveys. Furthermore, this study involved the person in charge of the media and the media supervisor, who was found to be using a purposive method. The study’s findings: (1) broadcast media (radio) represented through social media connectivity is a new ecosystem found in the element of broadcast radio proximity; (2) relationships through broadcasting technology are a solution in innovation as a convergence effort (broadcast-broadband) as a new broadcasting forum for private radio broadcasts, so to maintain the sustainability of the broadcasting (radio) ecosystem, technological and regulatory connectivity is needed in preparing a new forum for the broadcasting industry, especially radio broadcasting.